Electric sports cars and their impact on the component sourcing process. Issue 3 (27th June 2019) - Graham, Gary; Burns, Laird; Hennelly, Patrick; Meriton, Royston
Abstract : Purpose: The purpose of this paper is to explore how the sourcing process of the electric sports car sector is changing with respect to competitive advantage, required capabilities and emerging opportunism. Design/methodology/approach: The case study data collection covered the period from January till August 2017, which implies a total period of eight months. The empirical analysis implies a sequence of 20 conducted interviews with senior managers, team leaders and operational employees from various organizational departments and functions within Company A, various suppliers and experts from the automobile industry as well as primary and secondary literature. Findings: This work makes a contribution to the operations capability literature. It highlights the important role that sourcing will play to achieving strategic advantage in the electric sports car segment. Four key operational capabilities are emerging in the operating model. The first links to "capacity" and the ability of suppliers to be locally based so that they can deliver high-quality products and services in the minimum time (optimizing the "time-value" configuration). The second is the "design" of the supplier network. The third relates to "supplier management." Finally, the fourth capability relates to the ability of the firm to "integrate" and "align" their marketing and IT planning processes with their sourcing process. Research limitations/implications: Throughout the adaption of a sourcing framework and its extension to consider operational capabilities, the authors have begun to answer the research question of how the sourcing process for the supply of new electric powertrain components is being transformed. These initial findings, the authors intend to expand with more advanced case study work with the firm that will involve empirical modeling of process efficiency and inventory management. Practical implications: The work closes the gap regarding the need for practical application tools, designed for process managers, who are being confronted by turbulent, unpredictable and fast moving technological-driven market environments. Although the sourcing framework was developed to test the impact of the electric mobility trend, it can likewise be applied for the sourcing of components in other fast changing environments as well. Social implications: The paper raises the issues of the social role of the smart city planners in providing city spaces to enable the servicing of electric vehicles and to assist their production by developing the skills, capacity and capabilities of local city populations which will be needed to sustain and scale up any locally based operating model of electric vehicle production and servicing. Originality/value: Although much has been written about the technological challenges of electric vehicles and the rise of new entrants such as Tesla to challenge the dominance of the sports car manufacturer's very little work to data have explored the business-to-business (B2B) dimensions. The focus has been largely with the business-to-consumers (B2C) market.